Pengaruh Pertumbuhan Ekonomi, Upah Minimum Dan Tingkat Pendidikan Terhadap Penyerapan Tenaga Kerja Di Provinsi Bali - I Kadek Aditya Kusumanegara; Ni Luh Karmini (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2022)
Absorption of labor in the Province of Bali has become a problem in recent years. The unemployment rate in Bali continues to increase, and the number of people working in the informal sector continues to grow. Several factors cause the problem of labor absorption in Bali, one of the factors is the decline in the tourism industry. The purpose of this research to analyze how 1) the simultaneous effect of economic growth, minimum wage and level of education on labor absorption in the province of Bali; 2) the partial effect of economic growth, minimum wage and education level on labor absorption in Bali Province.This research used a quantitative approach. This type of data uses secondary data for the period 2017 – 2022 which was collected through the non-participant observation method. The research location is in the province of Bali which includes 9 regencies and cities. Data analysis techniques include descriptive statistics and multiple linear regression analysis using SPSS 25 software. The results show that: 1) economic growth, minimum wages and education level have a significant effect simultaneously on labor absorption in Bali Province; 2) economic growth and minimum wages have no partial effect on labor absorption, but the level of education has a significant effect on labor absorption. Based on the research results, it is expected that the government needs to increase the economic growth in the Province of Bali. This can be solved by developing the non-tourism sector, promoting investment, and empowering the small and medium enterprise sector.